Tokenization of Portuguese: resolving the hard cases - Branco, António Horta (2009)
This research note addresses the issue of ambiguous strings, strings of non-whitespace characters whose tokenization, depending of the specific occurrence, yields one or more than one token. This sort of strings, typically coinciding with orthographically contracted forms, is shown to raise the problem of undesired circularity between tokenization and tagging, under the standard view that tokenization takes place before tagging. The critical importance of this apparently minor, low-level issue results from the fact that these strings correspond mostly to functional words, that they are quite frequent, covering over 2% of a corpus, and that their careless treatment would introduce unrecoverable degradation of performance at a very early stage of language processing and that this degradation would trigger further and wider loss of accuracy in all subsequent processing stages. We argue for a resolution of this circularity on the basis of a new, two-level approach to tokenization. This approach is shown to be used also to improve the problem of sentence chunking at periods that are ambivalent between marking the end of an abbreviation and the end of a sentence